Contribuições à análise dinâmica da ação do vento em pilares de pontes via técnica do meio contínuo e método dos elementos finitos - Melo, Weslley Imperiano Gomes de (2019)
The improvement of structural analysis has been accelerating in the last two decades, primarily under Finite Element Method (FEM) modeling. Particularly with bridges, through such modeling, the dynamic effects are computed with greater rigor and reliability and due to the great agility of processing imposed by the market, the use of commercial software has become commonplace. In view of the use of such analysis and sizing programs, the structural engineer gains the practicality of simulating several load states, but must always have mechanisms for validation and verification of such results. Hence, in this thesis, the continuous medium technique (CMT) will be approached, restored and applied to the dynamic analysis of bridge columns, aiming at fostering a corroboration tool for simulations in commercial software (usually via FEM). The dynamic effects considered in the aforementioned columns through CMT were obtained with excellent precision, which allowed the validation of the following aspects: torsional bending phenomenon, wall panel theory, vibrations in structural cores braced by lintels, and elastic stability. In addition to the CMT exposure in the dynamic analysis, the postulation of flowcharts and calculation margins are evidenced from the point of view of matrix processing of differential equations, as well as the realization of the Wall Panel Theory Generalization (WPTG) procedures for the occurrence of non-orthogonal walls. Innovation takes place in the following: dynamic decoupling of the vibration of metal wall panels and reinforced concrete, proportional damping for structural rigidity partitioned in the core and in the bracing lintels, Maney equations in the balance of the lintels, and in the matrix condensation. Finally, for sections of reinforced concrete thin walls, subject to the bimoment, the calculation march and dimensionless tables are postulated to obtain the resistant steel area.